2014
DOI: 10.4047/jap.2014.6.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Degree of conversion of resin composite cured by light through a translucent fiber posts

Abstract: PURPOSEThis study evaluated the depth of cure of resin composite cured by light through a translucent fiber post.MATERIALS AND METHODSThe opaque plastic tubes in various lengths of 2, 4, 6, 8, 10, 12, 14 mm. were filled with resin composite in which two different translucent fiber posts were inserted into the center and photo-polymerized for 40 seconds. The degree of conversion of the cured composite at bottom surface were examined using Fourier transform infrared attenuated total reflection spectrometer (FTIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The DC values of the materials were measured using an FTIR spectrophotometer (IRPrestige-21; Shimadzu, Kyoto, Japan) with an attenuated total reflectance (ATR) unit (MIRacle; Pike Technologies Inc., Madison, WI, USA). 23 24 25 The absorbance spectra were obtained by scanning the specimens 20 times in the 1670-1550 cm -1 range with a resolution of 4 cm -1 . The aliphatic C=C bond (with a peak at 1638 cm -1 ) was used for the DC calculations, while the aromatic C=C bond (with a peak at 1608 cm -1 ) was used for the internal calibration.…”
Section: Methodsmentioning
confidence: 99%
“…The DC values of the materials were measured using an FTIR spectrophotometer (IRPrestige-21; Shimadzu, Kyoto, Japan) with an attenuated total reflectance (ATR) unit (MIRacle; Pike Technologies Inc., Madison, WI, USA). 23 24 25 The absorbance spectra were obtained by scanning the specimens 20 times in the 1670-1550 cm -1 range with a resolution of 4 cm -1 . The aliphatic C=C bond (with a peak at 1638 cm -1 ) was used for the DC calculations, while the aromatic C=C bond (with a peak at 1608 cm -1 ) was used for the internal calibration.…”
Section: Methodsmentioning
confidence: 99%
“…White and opaque additives in fiber posts may influence light transmission 14 . In this study these additives could contribute significantly to the TLRE.…”
Section: Discussionmentioning
confidence: 76%
“…Radiant exposure, which is sometimes also called radiant fluence, is the radiant energy received by a unit surface area or the irradiance of a surface integrated over the time of irradiance 12 . The effects of light curing on the DC of resin cement have been reported 8–10,13,14 . However, few studies have reported on the light intensity at various locations of different fiber posts 4,9,15–17 or the transmitted light radiant exposure (TLRE) through the post cross‐section of various systems, lengths, and diameters 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the two-step total-etch technique can achieve high bond strength, there are problems of high technical sensitivity, uncontrollable interface moisture and poor durability. Since the dentin bonding strength is generated after the formation of micro-mechanical retention by the resin monomer in the etched collagen fiber network, the quality of the hybrid layer (Urapepon, 2014) is directly related to the strength and durability, and therefore a uniform and dense hybrid layer can obtain better bonding effect (Marshall et al, 2010). The moisture content and the cured extent of the adhesive resin on the dentin surface will affect the quality of Journal of Zhejiang University-SCIENCE B (Biomedicine & Biotechnology) ISSN 1673-1581 (Print); ISSN 1862-1783 (Online) www.zju.edu.cn/jzus; www.springerlink.com E-mail: jzus@zju.edu.cn the mixed layer, and further study of these factors will contribute to the ability to form a good hybrid layer, thus contributing to achieving an ideal bonding effect.…”
Section: Introductionmentioning
confidence: 99%